The genome sequence of Langmaid’s Yellow Underwing moth, Noctua janthina (Denis & Schiffermüller) 1775 [version 1; peer review: 2 approved] - Gavin R. Broad (Wellcome Open Research)
We present a genome assembly from an individual male Noctua janthina (Langmaid’s Yellow Underwing; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence has a total length of 539.70 megabases. Most of the assembly (99.99%) is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.36 kilobases in length. Gene annotation of this assembly on Ensembl identified 12,089 protein-coding genes.